B2-Spline Interpolation Technique for Overset Grid Generation and Finite-Diﬀerence Time-Domain Method - Bong, S. Wee; Shafrida, binti Sahrani @ Shahran; Kismet, anak Hong Ping (EMW Publishing, 2018)
—In this paper, B2-spline interpolation technique for Overset Grid Generation and FiniteDiﬀerence Time-Domain (OGG-FDTD) method was developed. B2-spline or biquadratic spline interpolation oﬀers better accuracy than bilinear interpolation. Two-dimensional (2D) numerical simulations were carried out for electromagnetic (EM) ﬁeld analysis to measure the scattered ﬁelds for an unknown object in free space and dielectric medium. In this work, two antennas were utilised as transmitter and receiver sequentially to transmit microwave pulses and collect the scattered ﬁelds for an unknown object in OGG-FDTD lattice. In order to analyse the stability and eﬃciency of the proposed method, the scattered ﬁelds for the unknown object were investigated with error analysis. The results showed that the OGG-FDTD method with B2-spline interpolation gave lower relative error than bilinear interpolation with 0.0009% of diﬀerence in free space, 0.0033% of diﬀerence in Case A dielectric medium, 0.236% of diﬀerence in Case B dielectric medium, and 0.003% of diﬀerence in Case C dielectric medium. Besides, the Mean Square Error (MSE) for the OGG-FDTD method with B2-spline interpolation was also lower than the bilinear interpolation. Hence, it proves that the OGG-FDTD method with B2-spline interpolation has the ability to measure the scattered ﬁelds around an unknown object accurately. For future work, the proposed method can be applied to inverse scattering to detect and reconstruct buried objects with arbitrary shapes in a complex media.